Persepsi Mahasiswi Fakultas Ilmu Sosial Universitas Negeri Gorontalo Pada Pernikahan - Siti Nurchaliza Panai; Yowan Tamu; Feni Mariana (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Over time, the younger generation’s perspectives on marriage have shifted. Marriage, which was previously often positioned as a natural and immediate stage of a happy life, is now increasingly understood as a decision that requires careful consideration and reconsideration, contributing to a significant decline in marriage rates over the past decade, according to Statistics Indonesia (BPS). The younger generation no longer views marriage solely as a social obligation but also as a choice informed by emotional, economic, and mental readiness. This phenomenon is reflected, among other things, in the emergence of a trend known as Marriage is Scary, in which young people share their experiences and expectations about marriage. The purpose of this study is to describe the perceptions of female students of the Faculty of Social Sciences, Universitas Negeri Gorontalo, on marriage in general. The results of this study indicate that female students tend to adopt a more reflective, cautious attitude toward marriage. The conclusion of this study is that female students' interpretations of marriage do not lead to rejection but rather shift toward a more critical and reflective perspective.